2020
DOI: 10.21157/j.ked.hewan.v14i4.16751
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Hookworms Infection on Dogs in Sukabumi Regency, West Java Province, Indonesia

Abstract: Hookworms infection remains as an important parasitic infections affecting animal and human health worldwide. However, information on the prevalence and the risk factors of hookworm infection on dogs in Indonesia is very limited. A cross sectional study to estimate the prevalence and to identify risk factors of hookworms infection on dogs was conducted in rural area with different topography, Sukabumi Regency, Indonesia. A Total of 204 dog stool specimens were examined for hookworm eggs using simple flotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The previous study has reported that most dogs are raised as free-roaming, hunting dogs raised outdoors. Hunting dog owners in Sukabumi usually go hunting with their dogs twice a week, and infection might occur during these events [100]. During the life cycle of Ancylostoma caninum, a hookworm infection can occur during the latent stage, larval hypobiosis, fecal-oral transmission, and mammary-oral infection [101].…”
Section: Discussionmentioning
confidence: 99%
“…The previous study has reported that most dogs are raised as free-roaming, hunting dogs raised outdoors. Hunting dog owners in Sukabumi usually go hunting with their dogs twice a week, and infection might occur during these events [100]. During the life cycle of Ancylostoma caninum, a hookworm infection can occur during the latent stage, larval hypobiosis, fecal-oral transmission, and mammary-oral infection [101].…”
Section: Discussionmentioning
confidence: 99%
“…Its condition has led soil-transmitted helminths such as Ancylostoma spp. to be well-grown (Ridwan et al 2020).…”
Section: Introductionmentioning
confidence: 99%